Amoebiasis in Children: An Infection of Top Global Public Health Importance - Ashraf, Asfa; Iqbal, Muhammad Naeem (PSM Biological Research, 2020)
Foodborne diseases are important from public health as well as economic point of view. The infants, young children, the elderly, and the immunocompromised persons are particularly vulnerable to foodborne infections. Amoebiasis (amoebiasis, amoebic dysentery, amoebic enteritis) is an important foodborne protozoan disease that is primarily caused by Entamoeba histolytica. While amebiasis occurs worldwide, it is largely an infection of impoverished communities, particularly when sanitation is poor. A careful experimental study by Alshahethi et al (2020) describes the growing importance of amoebiasis in children as a foodborne disease of global public health concern.